Improved Theory of Clathrate Hydrates - Srikanth, Ravipati (2015)
The current theoretical understanding of thermodynamics of clathrate hydrates is based on the van der Waals and Plattew (vdWP) theory developed using statistical thermodynamics approach. vdWP theory has been widely used to predict the phase equilibrium of clathrate hydrates over the decades. However, earlier studies have shown that this success could be due to the presence of a large number of parameters. In this thesis, a systematic and a rigorous analysis of vdWP theory is per-formed with the help of Monte Carlo molecular simulations for methane hydrate. The analysis revealed that long range guest-water interactions and guest-guest interactions are important, Monte Carlo integration to is superior to the spherical shell approximation for the Langmuir constant calculation and even after inclusion of all the interactions and using Monte Carlo integration for Langmuir constant, the vdWP theory still fails to regress parameters correctly. This failure of vdWP theory is attributed to the rigid water lattice approximation. To address the rigid water lattice approximation, a new method is proposed. In the proposed method, the Langmuir constant is computed in flexible water lattice, by considering the movement of water molecules. The occupancy values predicted using the proposed method are in excellent agreement with the values obtained from Monte Carlo molecular simulations for variety of hydrates, methane, ethane, carbon dioxide and tetrahydrofuran(THF) hydrates . In addition to small guest molecules like methane, ethane etc. which are mod- heled as rigid, the method is extended for large guest molecules like propane and isobutane, using configurationally bias Monte Carlo method. The phase equilib-rium and occupancy along the phase equilibrium predictions from vdWP theory are compared with the exact phase equilibrium computed from Monte Carlo molecular simulations. This comparison is done for a wide variety of hydrate systems, single hydrates , binary hydrates and quaternary hydrate. In all the cases, the vdWP ...